Transition of DNA-HPV over time in HPV-infected women: a 7-year cohort study - Duong, Linh My; Tran, Dung Ngoc; Pham, Tam Thi; Vo, Trang Huynh; Tran, Hung Do; Lam, Tien Thi Thuy; Tran, Duc Long; Bui, Quang Nghia (Faculty of Medicine Universitas Indonesia, 2024)
BACKGROUND Approximately 99% of cervical cancer cases worldwide are associated with one of the high-risk human papillomavirus (HPV) types. This study aimed to determine the transition rate of DNA-HPV over time in women aged 18–69 years with HPV infection in Can Tho City, Vietnam, from 2013 to 2020. METHODS The 2-phase cohort study was conducted on 213 women between 2013 and 2020. Phase 1 involved a retrospective cohort study (2013–2018), and phase 2 included a prospective cohort study (2018–2020). HPV testing was performed using real-time polymerase chain reaction on cervical fluid. McNemar’s test was employed to compare differences in HPV transition between 2013 and 2020. RESULTS From 2013 to 2018, the transition, clearance, and non-transition rates were 17.1%, 65.8%, and 66.2%, respectively, revealing a significant difference in the number of HPV cases during this period (p = 0.007). From 2018 to 2020, the transition, clearance, and non-transition rates were 9.8%, 44.9%, and 82.2%, respectively. Overall, the DNA-HPV changes from 2013 to 2020 indicated rates of 14.3% for transition, 68.5% for clearance, and 67.1% for non-transition. A significant difference in HPV cases was found between 2013 and 2020 (p = 0.001). CONCLUSIONS The longer duration resulted in a more significant difference in the DNA-HPV transition among HPV-infected women.